INOVASI DIGITAL P2TP2A KABUPATEN KARAWANG DALAM PENCEGAHAN KEKERASAN TERHADAP ANAK - Sugianto, Mochamad Fadli; Azijah, Dewi Noor; Ramdani, Rachmat (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The development of digital technology has brought significant changes to public services, including in the area of child protection against violence. This study aims to analyze the digital communication strategy of P2TP2A Karawang Regency in preventing child abuse using Everett M. Rogers’ Diffusion of Innovations Theory as a framework. The research employed a qualitative approach through in-depth interviews with four groups of informants, namely social media managers, P2TP2A volunteers, the Secretary of DP3A, and service users, who were selected based on their direct involvement in managing or utilizing digital services. Data were analyzed using the interactive model of Miles and Huberman (1992), which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that digital media, particularly WhatsApp and Instagram, serve as the main innovations supporting case reporting, educational dissemination, and community outreach. The use of these digital platforms has proven to improve service accessibility and accelerate responses to cases of child abuse. However, several challenges remain, including limited human and technological resources, low levels of digital literacy among the community, and the complexity of handling cases that require cross-sectoral coordination. The novelty of this study lies in identifying the sustainability of digital communication strategies in Karawang Regency, which contributes to strengthening digital-based public service systems in child protection. Thus, it can be concluded that the diffusion of digital innovations implemented by P2TP2A Karawang has the potential to enhance the effectiveness of child abuse prevention, provided that it is supported by organizational readiness and improved community digital literacy.